2009
DOI: 10.1016/j.jmb.2009.05.078
|View full text |Cite
|
Sign up to set email alerts
|

Two Structurally Independent Domains of E. coli NusG Create Regulatory Plasticity via Distinct Interactions with RNA Polymerase and Regulators

Abstract: NusG is a conserved regulatory protein that interacts with elongating complexes (ECs) of RNA polymerase (RNAP), DNA, and RNA to modulate transcription in multiple and sometimes opposite ways. In E. coli, NusG suppresses pausing and increases elongation rate, enhances termination by E. coli ρ and phage HK022 Nun protein, and promotes antitermination by λN and in ribosomal RNA operons. We report NMR studies that suggest E. coli NusG consists of two largely independent Nand C-terminal structural domains, NTD and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

25
268
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(294 citation statements)
references
References 49 publications
25
268
1
Order By: Relevance
“…The Rho-binding domain in NusG has also recently been shown to interact with the S10 protein subunit of the ribosome, which has implications for the mechanism by which translation-uncoupled nascent transcripts may be subject to termination of their synthesis (9). Although null mutations in rho or nusG confer inviability in wild-type E. coli (11), missense mutations in the two genes are known that confer a transcription termination-defective (that is, polarity relief) phenotype (1,12,13,27,36).In the present study, we found that overexpression of the protein YdgT restores transcriptional polarity in the rho and nusG mutants and, furthermore, that the combination of rho, ydgT, and hha mutations confers extreme sickness in E. coli. YdgT (also called Cnu [30]) and Hha belong to the H-NS family of proteins (33), whose prototypic member H-NS participates in both regulation of transcription initiation and nucleoid structure (reviewed in references 16, 20, 23, and 59).…”
supporting
confidence: 45%
See 2 more Smart Citations
“…The Rho-binding domain in NusG has also recently been shown to interact with the S10 protein subunit of the ribosome, which has implications for the mechanism by which translation-uncoupled nascent transcripts may be subject to termination of their synthesis (9). Although null mutations in rho or nusG confer inviability in wild-type E. coli (11), missense mutations in the two genes are known that confer a transcription termination-defective (that is, polarity relief) phenotype (1,12,13,27,36).In the present study, we found that overexpression of the protein YdgT restores transcriptional polarity in the rho and nusG mutants and, furthermore, that the combination of rho, ydgT, and hha mutations confers extreme sickness in E. coli. YdgT (also called Cnu [30]) and Hha belong to the H-NS family of proteins (33), whose prototypic member H-NS participates in both regulation of transcription initiation and nucleoid structure (reviewed in references 16, 20, 23, and 59).…”
supporting
confidence: 45%
“…The Rho-binding domain in NusG has also recently been shown to interact with the S10 protein subunit of the ribosome, which has implications for the mechanism by which translation-uncoupled nascent transcripts may be subject to termination of their synthesis (9). Although null mutations in rho or nusG confer inviability in wild-type E. coli (11), missense mutations in the two genes are known that confer a transcription termination-defective (that is, polarity relief) phenotype (1,12,13,27,36).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Before testing for competition between RfaH and antisense RNA, we next asked if NusG might exhibit a similar effect. Although the NusG CTD does not inhibit NusG binding to RNAP (38) and full-length NusG has little effect on hairpin-stabilized pausing (12), we reasoned that high concentrations of NusG might compete for antisense RNA binding. Indeed, we found that 500 nM NusG partially suppressed pause stimulation by 1 M antisense RNA (Fig.…”
Section: Ssrna Upstream From An Exit Channel Duplex Enhances the Effementioning
confidence: 99%
“…The mechanism is absolutely dependent on the essential Rho protein that binds the nascent transcript and is then believed to signal RNA polymerase to terminate transcription, but there is no consensus as yet on its details (reviewed in references 1,3,14,40,41,43, and 48; see also references 21 and 31). As with their effects on transcription elongation, NusA and NusG have been reported to function antagonistically for Rho-dependent transcription termination as well, with NusG increasing its efficiency (7,8,11,29,35,38,52) and NusA decreasing it (8,27,(32)(33)(34); indeed, it has been reported that mutations in rho can suppress the inviability associated with the loss of NusA (58). On the other hand, Gottesman and coworkers (9,(52)(53)(54) have suggested that both NusA and NusG act cooperatively to promote Rho-dependent termination.…”
mentioning
confidence: 99%